1996
DOI: 10.1016/0960-0760(95)00239-1
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of rat steroid 5α-reductase activity in prostate and epididymis homogenates at neutral pH: Evidence for type I activity in epididymis

Abstract: Im m unocytochem ical studies and m R N A m easu rem en ts have show n th at the rat ep id id ym is-like the rat prostate-expresses both rat steroid 5a-reductase isozym es, i.e. type I and IL So far, enzym e activity m easurem ents in rat epididym is hom ogenates, how ever, do not support the presence o f type I 5a-reductase activity. Incubating hom ogenates o f both tissues w ith a wide range o f substrate concentrations, we were able to detect activity o f both isozym es in rat p rostate and ep id id ym is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Isozyme selectivity was examined in the rat liver at pH 7.0 and epididymis at pH 5.0. These organs express predominantly types 1 and 2 isozymes, respectively (Levy et al 1990;Normington and Russell 1992;Thigpen et al 1993;Span et al 1996). Z-350 inhibited both isozymes at the same concentration range with pIC 50 values of 8.44 and 8.86, respectively (Table 4).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Isozyme selectivity was examined in the rat liver at pH 7.0 and epididymis at pH 5.0. These organs express predominantly types 1 and 2 isozymes, respectively (Levy et al 1990;Normington and Russell 1992;Thigpen et al 1993;Span et al 1996). Z-350 inhibited both isozymes at the same concentration range with pIC 50 values of 8.44 and 8.86, respectively (Table 4).…”
Section: Resultsmentioning
confidence: 96%
“…Z-350 inhibited rat prostatic steroid 5α-reductase noncompetitively and inhibited steroid 5α-reductase in hepatic and epididymal tissue, which expresses predominantly types 1 and 2 isozymes, respectively (Levy et al 1990;Normington and Russell 1992;Thigpen et al 1993;Span et al 1996), with the same potency as in the prostate. These potencies of Z-350 were greater than that of finasteride, a subtype non-selective inhibitor for rat enzymes (Normington and Russell 1992), indicating that Z-350 was a potent and isozyme non-selective inhibitor of rat steroid 5α-reductase.…”
Section: Discussionmentioning
confidence: 94%
“…Moore and Wilson were the first to postulate the existence of two isozymes of 5␣-reductase, based on the presence of two distinct pH optima in 5␣reductase activity in human fibroblasts [27]. The acidic pH optimum of the type II isozyme is one of its most striking characteristics, which has been conserved in mouse, rat, monkey, and human [3,20,21,[26][27][28][29][30]. In this article, contrary to previously reported data by Liang et al [31], two pH optima of 5␣-reductase activity were found in the dog prostate.…”
Section: Discussionmentioning
confidence: 99%
“…The assay has been described and validated in detail in earlier papers [20,21]. In short, radiolabeled T was isotopically diluted to a range of 1.8 nM to 2.4 M (final concentration), dissolved in incubation buffer (400 l) in Pyrex culture tubes (borosilicate glass, 12 × 75 mm, Corning Inc., Corning, NY) and subsequently preheated at 37°C.…”
Section: ␣-Reductase Assaymentioning
confidence: 99%
See 1 more Smart Citation